Inflammasome-Associated Gastric Tumorigenesis Is Independent of the NLRP3 Pattern Recognition Receptor - West, Alice J.; Deswaerte, Virginie; West, Alison C.; Gearing, Linden J.; Tan, Patrick; Jenkins, Brendan J. (Frontiers in oncology, 2022)
Inflammasomes are important multiprotein regulatory complexes of innate immunity and have recently emerged as playing divergent roles in numerous inflammation-associated cancers. Among these include gastric cancer (GC), the third leading cause of cancer-associated death worldwide, and we have previously discovered a pro-tumorigenic role for the key inflammasome adaptor apoptosis-associated speck-like protein containing a CARD (ASC) in the spontaneous genetic gp130 F/F mouse model for GC. However, the identity of the specific pattern recognition receptors (PRRs) that activate tumor-promoting inflammasomes during GC is unknown. Here, we investigated the role of the best-characterized inflammasome-associated PRR, nucleotide-binding domain, and leucine-rich repeat containing receptor, pyrin domain-containing (NLRP) 3, in GC. In gastric tumors of gp130 F/F mice, although NLRP3 expression was elevated at the mRNA (qPCR) and protein (immunohistochemistry) levels, genetic ablation of NLRP3 in gp130 F/F : Nlrp3 -/- mice did not alleviate the development of gastric tumors. Similarly, cellular processes associated with tumorigenesis in the gastric mucosa, namely, proliferation, apoptosis, and inflammation, were comparable between gp130 F/F and gp130 F/F : Nlrp3 -/- mice. Furthermore, inflammasome activation levels, determined by immunoblotting and immunohistochemistry for cleaved Caspase-1, which along with ASC is another integral component of inflammasome complexes, were unchanged in gp130 F/F and gp130 F/F : Nlrp3 -/- gastric tumors. We also observed variable NLRP3 expression levels (mRNA and protein) among independent GC patient cohorts, and NLRP3 was not prognostic for survival outcomes. Taken together, these data suggest that NLRP3 does not play a major role in promoting inflammasome-driven gastric tumorigenesis, and thus pave the way for further investigations to uncover the key inflammasome-associated PRR implicated in GC.